Damage evolution and failure mechanisms under unloading tests of coal based on mining and excavation processes - Yi Wang; Xiangrui Meng; Guangming Zhao; Yingming Li; Qihang Zhang; Zhixi Liu (Alexandria Engineering Journal)
To investigate the damage characteristics and strength attenuation characteristics of coal, true triaxial single-side and double-side unloading tests of coal under various in-situ stresses were designed and conducted based on actual mining processes. The results indicated that within the depth range of 400–1600 m, the load-bearing capacity of the unloaded coal increased with rising in-situ stress, while its growth rate decreased progressively. As in-situ stress increased, the failure mode transitioned from tensile-dominated to tensile-shear composite failure by analyzing the velocity distribution under single-side and double-side unloading paths. The unloading damage ratio was quantitatively evaluated under different in-situ stress conditions. The simulation results indicated a critical tension-shear ratio threshold of 0.05 was identified in the AF-RA parameters. Additionally, an analytical formula was developed to predict ultimate load-bearing capacity through correlating lateral strain evolution with vertical stress variations during single-side and double-side unloading processes. The influence of end friction coefficients on failure morphology and stress redistribution were analyzed, and predictions were made for the bearing strength. These findings are of significant reference value for understanding unloading damage in coal and controlling the stability of coal pillars.